The decrease of non-complicated acute appendicitis and the negative appendectomy rate during pandemic - Ceresoli, Marco (Eur J Trauma Emerg Surg, 2021)
BACKGROUND: During pandemic, admissions for surgical emergencies dropped down dramatically. Also acute appendicitis decreased. The aim of the present study was to evaluate the change in volume and clinical presentation of patients with acute appendicitis during pandemic and the variation in treatment. METHODS: This is a retrospective study of patients admitted in 11 Italian hospital for acute appendicitis during the lockdown period (March–April 2020) compared with the same period of the previous 2 years (2018–2019). The number and the rate of complicated and non-complicated acute appendicitis were recorded and compared between the two study periods; non-operative vs operative treatment and negative appendectomy rate were also recorded. RESULTS: The study included 532 patients, 112 in the study period and 420 in the control period; Hospital admission for acute appendicitis dropped by 46% (OR 0.516 95% CI 0.411–0.648 p < 0.001) during the 2020 lockdown. The number of complicated acute appendicitis did not change (− 18%, OR 0.763 95% CI 0.517–1.124 p = 0.1719), whereas the number of non-complicated acute appendicitis significantly decreased (− 56%, OR 0.424 95% CI 0.319–0.564 p < 0.001). Non-operative treatment rate remained similar (12.1% vs. 11.6% p = 0.434). The negative appendectomy rate also significantly decreased (6.1% vs. 17.3%, p = 0.006). CONCLUSIONS: The present study found a significant reduction of both admissions for non-complicated acute appendicitis and negative appendectomy rate during the pandemic period. Conversely, admissions for complicated acute appendicitis did not change. Trial registration: NCT04649996.